PENGAMBILAN KEBIJAKAN RASIONAL OLEH PEMERINTAH TINGKOK TERHADAP ETNIS UIGHUR DI XINJIANG 2014 - 2019 - Fatimatuh Zahrah (Journal of International Relations, 2023)
In 2014 an act of terror shocked Chinese citizen. After investigation, it was found that this crime was committed by few Uighurs’ descendants. This situation had made China strengthened its national security by implementing Strike Hard Against Extremist Terrorism and Reeducation Policies in Xinjiang which predominantly inhabited by Uighurs. At first both policies were directed to maintain Chinese national security, but the aim shifted when China launched One Belt One Road program and fortifying it control in Xinjiang in order to maximize economic beneficial. This research use literature review as data gathering technic complemented by Decision Making Theory and National Security Concept to explain the reason of Chinese Government policy toward the Uighurs. The act of terror in 2014 who committed by few Uighurs’ triggered President Xi Jinping to focusing in security sector in order to maintain national stability. Decision to enforce Strike Hard Against Extremist Terrorism and Reeducation Policies at first intended to maintain security and educate the people shifted as One Belt Road commenced. Chinese government sacrifices Uighurs in order to maximize national economic benefits.